2021
DOI: 10.13189/ujer.2021.090304
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study of Students' Learning Progression in Algebra

Abstract: This study explored the learning progression in Algebra of students from a cohort perspective and individual perspective. Utilizing the cross-sectional and longitudinal research methods and employing the Rasch measurement modeling, the progress in the Algebraic performance of the 592 students (Grade 8, Grade 9 and Grade 10) in a school division in the Philippines was examined four times in around one academic year. Analyses revealed that the students only have a low level of performance in Algebra. Through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Most students concluded that Mathematics is a complicated subject (Kislenko et al). Many studies have been conducted to identify challenges or difficulties hindering the appreciation of mathematics and the acquisition of skills the students need (Cadorna, Cadorna, and Taban, 2021). Lastly, Darvishzadeh, Shahvarani, Alamolhodaei and Behzadi (2018) mentioned that experiences in teaching mathematics have indicated that most students have weaknesses in solving mathematical problems.…”
Section: Introductionmentioning
confidence: 99%
“…Most students concluded that Mathematics is a complicated subject (Kislenko et al). Many studies have been conducted to identify challenges or difficulties hindering the appreciation of mathematics and the acquisition of skills the students need (Cadorna, Cadorna, and Taban, 2021). Lastly, Darvishzadeh, Shahvarani, Alamolhodaei and Behzadi (2018) mentioned that experiences in teaching mathematics have indicated that most students have weaknesses in solving mathematical problems.…”
Section: Introductionmentioning
confidence: 99%
“…Children's artifacts were analyzed to examine their coding practices and their relation to CT, thus providing useful insights about each cohort. The study methodology is aligned with an increasing corpus of research which reports that such cross-sectional studies on children's understanding and skills at different developmental stages and ages can contribute to the development of hypothetical progressions for instructional pathways and curriculum planning (e.g., Cadorna et al, 2021;Duncan et al, 2009;Duschl, 2019).…”
mentioning
confidence: 99%